Owning and operating costs of passenger car in Malaysia - Syarifah Nursyarafina, Syed Hussein (2017)
The study of owning and operating costs of passenger car is carried out to determine the efficiency cost between using private vehicle and public transport. The costs involved are owning, operation and maintenance cost. First of all, need to know the model of the car with and the owning cost included the price when purchased, year manufacture, mileage used, road tax and insurance. While for operation and maintenance, based on the owner of the car either get a service from centre or workshop and depends the price of the gasoline. It will be a different cost but not a big gap. Each element need to compare between each model of the car in per kilometre. The purposes of study the cost is to compare and define the travel cost. Purposed comparison happened between private and public is to increase the awareness the environmental and economic advantages of using bus on a regular basis. In this study also can show that demand of owning a vehicle is increase year by year due to economic and needs. But still using public transport can gives more advantages than disadvantages.